The complete idiot's guide to the chemistry of love - Fisher, Maryanne; Costello, Victoria (Indianapolis, IN : Alpha, 2010)
Examines the neurological, biochemical, and evolutionary reactions that take place in the body to create feelings of desire-- and more!
Phases of love. Heart, head, and glands ; The evolution of desire ; Who's steering this ship? ; How we're hooked: five senses ; When chemistry meets psychology ; Lust: short-term attraction ; The long-term relationship -- Sex is what we do. Growing up ; Chemistry of sexual arousal and orgasm ; Female sexual response ; Male sexual response -- Enhancers and detractors. Sex enhancers ; Sex inhibitors ; Staying fit for sex -- Friends, foes, and family. Other relationships ; The chemistry of awe: baby chemistry ; Love chemistry for mature couples ; Putting it all together.
Includes bibliographical references (p. [227]-228) and index.
Keywords: Love; Love -- Physiological aspects; Sex; Sex differences